Notion of New Structure of Uncertain Sequences Using Δ-Spaces - Mashael M. AlBaidani (Journal of Mathematics)
The object of this paper is to introduce a new approach of Δ-operator on the theory of uncertainty using sequence spaces. Also, some structural properties will be studied. Moreover, inclusion relations concerning the newly constructed spaces of this paper will be taken care of.